High-temperature creep property and life prediction of aluminized AISI 321 stainless steel after annealing diffusion treatment. (October 2021) - Li, Wei; Chen, Huitao; Huang, Weiying; Chen, Jian; Li, Cong; Xu, Dongliang; An, Shuaipeng; Zhang, Shengde; Yang, Huiting
Highlights: Aluminizing and annealing process was applied to 321 stainless steel. Shorten creep life was observed in aluminized steel. Twin annihilation is developed in annealing sample during creep deformation. Increased creep performance was caused by annealing process. θ -projection method is more accurate and prominent for creep life prediction. Abstract: In this paper, pack cementation has been applied to prepare aluminized coatings on AISI 321 stainless steel. The effect of aluminizing process and subsequent annealing treatment on the creep properties and life prediction of AISI 321 was investigated at 620 °C. The results reveal that the coatings of aluminized steel are incorporated by a top inhomogeneous Al2 O3, a Fe-Al intermetallic compound layer and subsequent Fe(Al) solid solution layer. In addition, the coatings thickness increased apparently after annealing. The reduction of effective bearing area due to the formation of defects around NiAl at coatings and the intrinsic brittle nature of the coating are responsible for the degradation of creep lives for aluminizing steel in comparison to that of as-received steel. During creep deformation, M23 C6 and TiC precipitated at austenitic grain interior would produce dislocations radially, indicating deformation mechanism of aluminized steel domains by dislocation–dislocation interactions. However, annealed steel exhibits a discernable improved creep performance since twin boundary factions induced by annealing are as twice as before. In the creep process, tangled dislocations interact with twin boundaries, leading to the formation of weaken zones within twined region. Compared with other theories, θ -projection method has outstanding ability to predict the creep life of materials due to its adequate parameters defined to describe three typical stages of creep curve admirably.